Addressing Persistent Forest and Land Fires in Indonesia : Institutional and Expenditure Review of Fire Management - World Bank (World Bank, Washington, DC, 2021)
Indonesia has experienced two major forest and land fire events in the past five years. According to government data, the 2015 and 2019 fire episodes led to the burning of around 2.6 million hectares and 1.6 million hectares,1 respectively. The fires and the resulting haze in 2019 led to significant negative economic impacts and direct damage to assets and losses to Indonesia’s infrastructure, and to its agriculture, industry, trade, tourism, transportation, health, and environmental sectors. Unlike the wildfires in boreal forests of North America, land-based fires in Indonesia are man-made. Fire episodes recur annually because fire is considered as the cheapest method to prepare lands for cultivation, or to claim lands in areas with conflict, where landownership is uncertain, and where enforcement is weak. Without measures to control land burning, fires can spread uncontrollably, especially during extended dry seasons induced by climate patterns. When fires burned drained carbon-rich peatlands, they release greenhouse gas emissions that drive climate change. This report discusses elements critical to developing an IFM strategy in Indonesia, including the identification and analysis of: (1) fire-prone locations, (2) major drivers of fires, (3) central government institutions with mandates linked to drivers of fires, (4) program framework and related spending on fire management, and (5) the role of local institutions and an (‘cluster-based’) integrated approach at the landscape level.